Makers of Pervasive Systems and Crafts - Amft, Oliver; Baker, Mary (IEEE Pervasive Computing, 2019)
We recently had the pleasure of interviewing researchers in electronics and materials for pervasive systems, as well as researchers, practitioners, and digital tool builders in crafts such as music and food. We have separated the conversations into two interview digests. The first highlights important topics for future research in pervasive systems and provides guidance for new investigators and entrepreneurs interested in the area. The second focuses on the interaction between crafts and new pervasive technologies to discover the ways technology is amplifying tradition or helping to create new hybrid crafts-crafts that combine the physical and digital.
CRIS-Team WoS Importer:2020-02-14